الشمول المالي في البلدان العربية مع الإشارة لحالة الجزائر (Journal of Economics and Management Research, 2023)
مع تكامل الاقتصاد العالمي، تم إيلاء اهتمام كبير للشمول المالي، الذي أصبح منذ ذلك الحين موضوعًا شائعًا ليس فقط للمؤسسات المالية العالمية مثل البنك الدولي وصندوق النقد الدولي، ولكن أيضًا للحكومات والجهات التنظيمية، ونظرًا لأن الشمول المالي يكتسب هذا المستوى من الاهتمام في جميع أنحاء العالم، حيث يتم تنفيذه في البلدان النامية، اهتمت ورقتنا بدراسة الشمول المالي وواقعه في البلدان العربية وبالأخص الجزائر. وتشير النتائج الرئيسية في هذه الدراسة إلى أنه رغم الجهود المبذولة في الدول العربية لتعزيز الشمول المالي ما زال لم يواكب المستوى الذي يشهده باقي دول العالم، ومنها الجزائر، رغم التحسن الذي عرفه خلال السنوات الأخيرة، إذ لا تزال ضمن أقل المجموعات الجغرافية من حيث مستويات الشمول المالي. As the world economy became integrated, a great attention has been given to financial inclusion, which became since then a trending topic not only for global financial institutions as the World Bank and the IMF, but also for governments and regulators, as financial inclusion is gaining that level of attention worldwide, implementing it in the developing countries, our paper is interested in studing the financial inclusion and its reality in the Arab countries, especially Algeria. The key findings in this study indicate that despite the efforts made in Arabe countries to enhance financial inclusion, it is still not keeping pace with the level witnessed by the rest of the world, Including Algeria, despite the improvement it has experienced in recent years, as it is still among the lowest geographical groups in terms of levels of financial inclusion.